Using the free listing technique to study consumers’ representations of traditional gastronomy in Argentina - Cuffia, Facundo (2023)
The aims of this research were (i) to study with a sample of Argentine consumers the representations of traditional gastronomy through the free listing method; (ii) to identify consumers’ typologies according to their representation of traditional gastronomy; and (iii) to establish some methodological implications using the free listing in the study of the gastronomic field. A survey was conducted in which 249 Argentines from the Littoral area were recruited. Through a free listing task, participants were asked to mention the main foods or dishes of Argentina’s gastronomy. Twenty-eight foods, dishes or food categories were obtained that are part of the representations of Argentina’s gastronomy. The results showed a strong connection between gastronomy and the representations of the consumers with the “Asado” (CSI = 0.289, Smith = 0.613), the traditional and characteristic food of Argentine gastronomy. Three groups of consumers were identified, presenting differences in the representation of traditional gastronomy (p < 0.05). This work is pioneering for studying gastronomy representations from the consumers’ language through the free listing method using the case of traditional Argentine gastronomy. Future directions of free listing in the gastronomic field are identified and discussed.